2012
DOI: 10.7314/apjcp.2012.13.4.1383
|View full text |Cite
|
Sign up to set email alerts
|

Perception, Attitudes, Preparedness and Experience of Chemotherapy-Induced Alopecia among Breast Cancer Patients: a Qualitative Study

Abstract: Objectives: Regardless of its negative impact on quality of life, little is known about the importance of alopecia from the patients' perspective. This study aimed to explore the whole experience of chemotherapyinduced alopecia among Korean breast cancer patients including perception, attitudes, preparedness, and changes after alopecia. Methods: Patients expected to experience or had experienced alopecia were recruited at a tertiary hospital in Seoul, Korea. Semi-structured in-depth interviews were performed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(102 citation statements)
references
References 18 publications
(24 reference statements)
5
97
0
Order By: Relevance
“…In contrast, multiple severe side effects and hepatotoxicity were the least preferred health states (Sun et al, 2002). Alopecia was also described as a distressing side effect by breast cancer patients as it had consistently affected their QOL and body image (Lemieux et al, 2008;Kim et al, 2012). As emphasized by studies since 1980's,…”
Section: Side Effects Of Chemotherapy Among Cancer Patients In a Malamentioning
confidence: 99%
“…In contrast, multiple severe side effects and hepatotoxicity were the least preferred health states (Sun et al, 2002). Alopecia was also described as a distressing side effect by breast cancer patients as it had consistently affected their QOL and body image (Lemieux et al, 2008;Kim et al, 2012). As emphasized by studies since 1980's,…”
Section: Side Effects Of Chemotherapy Among Cancer Patients In a Malamentioning
confidence: 99%
“…Alopecia forced them to reduce outside daily activities to conceal it. Patients were worried that hair might not grow back (Kim et al, 2012). Although losing hair usually will recover over time, a report of adult survivors of childhood cancer documented that in fact 10% of survivors were affected by prolonged alopecia after treatment completion (Kinahan et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they reported that they would not have undergone treatment if they knew of the suffering that the treatment would cause. [21] Another study carried out on 100 oncology patients, the most common effects were: alopecia, fatigue, negative impact on the family or spouse, work or domestic activities, as well as effects on the social and sexual life. [11] This induces us to reflect on side effects with negative impact on the patient's quality of life.…”
Section: Published By Sciedu Pressmentioning
confidence: 99%